مساهمة في تحديد بعض أنواع الشعريات الطفيلية Parasitic Capillaria (ممسودات) عند أسماك الكارب العادي في مزرعة السن. (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
أجريت الدراسة على 420 سمكة كارب عادي بأعمار من 40 يوم حتى سنتين، أُخِذَت العينات عشوائياً بفاصل زمني لا يقل عن 15 يوم من مزرعة السن خلال الفترة 4-10-2000 حتى 2-10-2001. تم عزل وتصنيف نوعين من الشعريات الطفيلية تنتمي تصنيفياً للجنس Capillaria هما:      Capillaria amurensis & Capilaria  tomentosaوجدت في القسم الأمامي من لمعة الأمعاء، سُجِّلَ هذان النوعان لأول مرة في سوريا في دراستنا هذه. اختلف النوعان في نسبة إصابتهما (خمجهما) للأسماك وكان النوع Capillaria tomentosa الأكثر انتشاراً بنسبة إصابة%8.33 وشدة إصابة 1.51 دودة/ سمكة. أبدت هذه الطفيليات علاقة مباشرة مع بعض المؤشرات البيئية خصوصاً الحرارة. A total of 420 carp fish (Cyprinus carpio L.) aged between 40 days to more than two years old were studied during the period lasted from 4. October 2000 to 2. October 2001, Samples were collected randomally nearly every fortnight, from Al - sin fish farm. Isolation and classification were performed for two parasitic species of parasitic Capillaria which were Capillaria tomentosa and Capillaria amurensis deposited in anterior fragment of intestinal lumen, These two species were classified for the first time at the syrian coast fresh water resources in this study. These parasites were varied in the rates of their fish-infection whereby Capillaria tomentosa was more distributed in infection rate 8.33% and infection intensity 1.51 worm/fish. Parasites have shown direct relationship with some invironmental factors especially temperature.